Peritoneovenous shunting is an effective treatment for intractable ascites. Issue 954 (5th April 2005) - Sooriakumaran, P; McAndrew, H F; Kiely, E M; Spitz, L; Pierro, A
Abstract : Aim and methods: A retrospective review was carried out of children undergoing peritoneovenous shunting for intractable ascites. Results: 11 children, aged 3 months to 12 years (median 31 months) underwent peritoneovenous shunting over the past 17 years. The duration of ascites ranged from one month to 2.5 years (median two months). The primary pathology consisted of previous surgery in eight (three neuroblastoma, one renal carcinoma, one hepatoblastoma, one adrenal teratoma, one renal artery stenosis, and one diaphragmatic hernia), and cytomegalovirus hepatitis, lymphatic hypoplasia, and lymphohistiocytosis in one patient each. All patients had failed to respond to previous treatment including peritoneal drainage in six patients, diuretics in five, and parenteral nutrition in five. There were no intraoperative problems. Postoperative complications included pulmonary oedema in three patients, shunt occlusion in three, infection in two, and wound leakage in one. Ascites resolved after shunting in 10 patients. Five shunts were removed one to three years after insertion without recurrence of ascites. Three others are free of ascites with shunts in place for less than one year postoperatively. Three children died from their underlying disease: two after resolution of ascites (neuroblastoma) and one in whom the ascites failed to resolve (lymphohisticytosis). Conclusions: Peritoneovenous shunting is an effective treatment for symptomatic intractable ascites in children (10 of 11 successful cases in this series). Elective removal of the shunt after one year is recommended.